The Role of Workload on Intentions to Leave Work, Mediated by Work Stress and Moderated by Social Support - Liani Cynthia; Rita Markus Idulfilastri; Zamralita Zamralita (Universitas KH. Abdul Chalim Mojokerto, 2025)
Generation Z is the next generation of the nation and they will be the ones to take over the industrial world. It is known that generation Z has twice the tendency to experience psychological stress compared to other generations. High workload often makes individuals tend to have the intention to leave the company. Workload can lead to work stress experienced by individuals. Work stress can have several impacts on the organization including the employee concerned not coming to work and leaving the organization. The existence of social support in an organization is expected to help minimize all the pressure felt by generation Z employees. The purpose of this study was to determine the role of workload on work exit intention in generation Z employees mediated by work stress and moderated by social support. The characteristics of participants in this study are generation Z, aged 18 to 27 years, have a minimum work experience of six months totaling 254 people. This study uses the Turnover Intention Scale measuring instrument from Mobley et al. (1978), National Aeronautics and Space Administration Task Load Index (NASA-TLX) from Hart and Staveland (1988), Job Stress Scale (JSS) from Parker & Decotiss (1983), and Multidimentional Scale of Perceived Social Support (MSPSS) from Dahlem et al. (1991). The results of this study indicate that workload has a significant influence on work performance. The results of this study indicate that workload has an influence on intention to work with a value of R2 = 0.428. Then, job stress is proven to mediate between workload and intention to leave. Finally, social support is proven not to moderate between workload and intention to leave.